Acute changes of left ventricular function during surgical revascularization by 3D speckle tracking. Issue 4 (19th March 2021) - Chen, Wanwen; Ortiz‐Leon, Xochitl A.; Posada‐Martinez, Edith Liliana; Pereira, Jason; Dewar, Michael L.; Darr, Umer; Geirsson, Arnar; Sugeng, Lissa; Zhu, Qingbing
Abstract: Background: Detecting early impact of coronary artery bypass grafting (CABG) on left ventricular (LV) function is important because such measures may contribute to meaningful improvement in clinical outcomes. We aimed to gain knowledge about acute changes of LV performance during surgical revascularization using three‐dimensional speckle tracking echocardiography (3D STE). Methods: Thirty‐five patients scheduled for CABG surgery who underwent intraoperative transesophageal echocardiography (TEE) were enrolled (mean age 68.9 ± 7.3 years). TEE was performed before and after surgery, as well as before and after grafting. 3D LV ejection fraction (LVEF), tissue motion annular displacement (TMAD) of the mitral valves, 3D global longitudinal strain (GLS), global circumferential strain (GCS), twist, and torsion were quantified. Regional longitudinal strain (LS) was calculated based on coronary perfusion territories in a 16‐segment LV model. Results: Despite the absence of change in TMAD and 3D LVEF, 3D GLS (−18.6 ± 4.3% at baseline vs −16.0 ± 4.0% after surgery, P  = .01) was significantly decreased, followed with no significant effect on GCS, twist, and torsion during surgery. 3D GLS correlated significantly with 3D LVEF (r between −0.34 and −0.51, P  < .05 for all) under the whole operation. Territorial LS did not increase immediately after surgery. Conclusion: 3D speckle tracking imaging allows for detailed and direct evaluation of myocardial deformation, though impaired LV longitudinal function is still apparent immediately after surgery. GLS is more sensitive to an acute reduction in LV function than conventional parameters, which can be potentially useful for serial monitoring of functional recovery.